PANCASILA SEBAGAI NORMA DAN HUKUM YANG MENDASAR DALAM PRESPEKTIF YURIDIS - Yenika Sari; Shinta Karina Putri; anita trisiana (RESEARCH FAIR UNISRI, 2022)
A day after independence proclamation indonesia exactly date 18 august 1945 travel pancasila as a basis nationality the bottom of the state in a juridical manner started. In pencaturan ideology the world expanded in developing countries including indonesia, is uneasiness to formulate the future. This confirms that pancasila is fundamental and having a very important role in the formation of the republic of indonesia. The problems are not maybe can be completed in a unilateral manner, in accordance with article 1 paragraph ( 3 ) of Undang-UndangDasar 1945 constitution that indonesia is a country law. Should all parties back to see or tracing pancasila as a basis the state and as the norm of legal basis indonesia.Put back pancasila proportionally and contextual with the spirit of the times and affirmed its position pancasila in the indonesian law is one reason very natural to revive diskursuspancasila. Through the literature study of scientific work such as books, journal, and other study and the regulations perundang-undangan related to the theme research is the way said the problems and it was one of approach juridical normative with data collection method. A norm legal basis indonesia is as perspective juridical pancasila who qualitatively all the data collected should then new analysis. Norms and normal legal basis and ways law as stipulated in the pembukaanundang-undangdasar 1945 is the source of orderly indonesia, this position requires the formation of positive law to reach idea in pancasila used as an examiner positive law that is the result that research shows of law indonesia in perspective juridical.